Excellent cryogenic optical thermometry based on green up-conversion of Ho3+-doped perovskite Na0.5Bi0.5TiO3 ceramics. Issue 4 (5th January 2021) - Wang, Yuzhen; Wang, Yanan; Ma, Chaoyang; Feng, Zhe; Zuo, Chuandong; Ye, Wanggui; Zhao, Chong; Li, Yanbin; Wen, Zicheng; Cao, Zhiquan; Cao, Zhijun; Shen, Xiaofei; et al.
Abstract : An excellent cryogenic optical thermometry performance can be obtained by the green up-conversion luminescence of Ho 3+ -doped Na0.5 Bi0.5 TiO3 ceramics. Abstract : In this study, various Na0.5 Bi0.5 TiO3 :0.5 at% Ho 3+ (NBT:Ho) ceramics with different Yb 3+ ion doping concentrations were synthesized by a conventional solid-state reaction method. Under the irradiation of a 980 nm laser, the NBT:Ho sample exhibited four distinguished emission bands centered at 525, 548, 656, and 753 nm. By co-doping Yb 3+ ions into NBT as the sensitizers, the up-conversion luminescence of Ho 3+ ions was greatly enhanced. The mechanism for up-conversion luminescence was determined to be a two-photon absorption process. The DFT simulations revealed that the Ho 3+ 4f orbitals pass through the Fermi level and thus f–f transitions could be highly sensitive to temperature variation. Green emissions at 525 and 548 nm were ascribed to the two thermally coupled excited states 5 F4 and 5 S2 transferring to the ground state 5 I8, respectively. The temperature-dependent population between 5 F4 and 5 S2 could be interpreted by Boltzmann's distribution in the range of 167–377 K. The relative sensitivities were calculated to be 6.14% K −1 at 167 K and 1.03% K −1 at 377 K, and the corresponding absolute sensitivities were estimated to be 0.09 × 10 −3 K −1 and 2.11 × 10 −3 K −1, respectively. The temperature resolution was calculated to be about 0.053 K at 167 K and 0.319 K at 377 K. The excellent repeatability of the NBT:Ho 3+ ceramics was demonstrated by means of successive heating–cooling cycles in the range of 167–377 K. The above investigation results demonstrate the promising application of NBT:Ho in cryogenic optical thermometers.